SISTEM PENJADWALAN BIMBINGAN BELAJAR BERBASIS WEB MENGGUNAKAN ALGORITMA GENETIKA - Adinda Yuli Setiani; Ahmad Heru Mujianto; Andriani, Anita; Sri Widoyoningrum (Inovate, 2024)
Scheduling is the act, process, and method of scheduling or entering schedule data involves preparingactivities for a specific period while considering a number of variables, including classes, teachers, and time.The scheduling procedure at Omah Sinau Tutoring is still done manually. This causes inefficient use of timeand will affect the standard of education received by students. Omah Sinau Tutoring uses genetic algorithmsas an optimization technique to create schedules in order to overcome this problem. Many optimizationproblems can be solved with genetic algorithms. The benefits of analogies between the mechanisms ofnatural selection and the mechanisms of interbreeding, mutation, and other features inherent in the geneticalgorithm process serve as the basis for genetic algorithm solutions, rather than mathematical calculations.Genetic algorithms are capable of handling complex problems that are challenging to tackle by traditionalapproaches. The number of populations, generations, crosses, and mutations that can be handled by thegenetic algorithm to solve the problem by generating optimal scheduling and reducing the time needed tocreate the schedule so that the process of creating it becomes effective and efficient are the parameters used,based on the results of the tests conducted.Keywords: scheduling, genetic algorithm, tutoring.